2009
DOI: 10.1016/j.brainres.2009.07.101
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-PK catalytic subunit regulates Bax-mediated excitotoxic cell death by Ku70 phosphorylation

Abstract: DNA repair deficiency results in neurodegenerative disease and increased susceptibility to excitotoxic cell death, suggesting a critical, but undefined role for DNA damage in neurodegeneration. We compared DNA damage, Ku70-Bax interaction, and Bax-dependent excitotoxic cell death in kainic acid-treated primary cortical neurons derived from both wildtype mice and mice deficient in the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) encoded by the Prkdc gene. In both wildtype and Prkdc−/− neurons, kain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…138 The link between Ku70 and cell death is also noted in a neurodegenerative disease model where DNA-PK CS links DNA damage to Bax-dependent cell death, by phosphorylating Ku70 on serines 6 and/or 51, initiating Bax translocation to the mitochondria and directly activating a pro-apoptotic Bax-dependent death cascade. 139 These reports complement the described role of DNA-PK particularly in regard to the maintenance of chromosomes. As previously considered, telomerase-deficient (Terc -/-) mice show widespread germ cell line apoptosis, however a Terc -/-DNA-PK CS -/-double knockout mouse strain does not show increased apoptosis indicating a clear role of DNA-PK CS in mediating apoptosis (that is independent of Ku) in cell lines with critically shortened telomeres.…”
Section: Summary and Future Directionssupporting
confidence: 57%
“…138 The link between Ku70 and cell death is also noted in a neurodegenerative disease model where DNA-PK CS links DNA damage to Bax-dependent cell death, by phosphorylating Ku70 on serines 6 and/or 51, initiating Bax translocation to the mitochondria and directly activating a pro-apoptotic Bax-dependent death cascade. 139 These reports complement the described role of DNA-PK particularly in regard to the maintenance of chromosomes. As previously considered, telomerase-deficient (Terc -/-) mice show widespread germ cell line apoptosis, however a Terc -/-DNA-PK CS -/-double knockout mouse strain does not show increased apoptosis indicating a clear role of DNA-PK CS in mediating apoptosis (that is independent of Ku) in cell lines with critically shortened telomeres.…”
Section: Summary and Future Directionssupporting
confidence: 57%
“…In this scenario, the specific post-translational modification of Ku70 could account for both its dual functions, in DNA repair and in suppressing Bax-mediated apoptosis, and decide the cell fate in a condition of severe DNA damage. Moreover, it is worth mentioning that Liu et al have demonstrated that, on DNA damage induced by kainic acid, Ku70 is phosphorylated by DNA-PKcs, resulting in Bax release and translocation into the mitochondria to initiate apoptosis (46). There is further evidence highlighting Ku's involvement in the crosstalk between the DNA repair machinery and the DNA damage signaling regulators controlling apoptosis.…”
Section: Kumentioning
confidence: 99%
“…staurosporine and kainic acid (Chechlacz et al, 2001;Vemuri et al, 2001;Liu et al, 2009). We therefore sought to determine how DNA-PKcs functions during the neural DDR, and additionally in the context of the related kinases ATM and ATR.…”
Section: Dna-pkcs Loss Hypersensitizes To Apoptosis In the Neocortex mentioning
confidence: 99%